The Development of ARCS-Based Economic E-Book Media for Senior High School - Saputri, Kartika Yunita; Santoso, Sigit; Hindrayani, Aniek (Fakultas Ekonomi, Universitas Negeri Semarang, 2021)
This study aimed to determine the appropriateness of ARCS-based economic e-books on international trade material in the class XI IPS of Senior High School in terms of experts' assessments and students' responses to e-book products developed. This study used the Borg & Gall development model which was modified into 10 stages, namely: 1) research and information gathering; 2) planning; 3) early e-book product development; 4) initial trials; 5) revision I; 6) main trials; 7) revision II; 8) operational trials; 9) revision III; 10) dissemination. The research was conducted in class XI of Senior High School in Surakarta. Data collection methods in this study used validation sheets and questionnaire sheets which were analyzed descriptively. The results showed the feasibility of an economic e-book based on ARCS qualified